Pengaruh Nilai Perusahaan Ditinjau Dari Segi Pertumbuhan Perusahaan pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Mursalini, Wahyu Indah; Jolistika, Rani; Sriyanti, Esi (Pustaka Galeri Mandiri, 2025)
This research aims to determine the effect of Company Value from the perspective of Company Growth on manufacturing companies listed on the IDX from 2019 to 2023. The sample used in this study consists of 10 samples from a population of 19 companies in the Automotive sub-sector listed on the IDX for the period 2019-2023. The method used in this study is purposive sampling. The data analysis techniques used are classical assumption tests, the coefficient of determination test (R2), multiple linear regression, and hypothesis testing. The results of the study show that partially, Company Growth does not have a significant effect on Company Value, with a significance value of 0.335 > 0.05. Based on the results of the third hypothesis test using the F test, it is known that the sig value is 0.000 < 0.05, so it can be concluded that the independent variable has an effect on the dependent variable, meaning that Company Growth collectively has a significant effect on Company Value. In this study, the variable Company Growth can only explain 80.7% of the Company Value according to the results of the coefficient of determination test (R²), indicating a low proximity between the dependent and independent variables. Meanwhile, the remaining 19.3% is influenced by other variables outside the model discussed in this study.